PSYCHOLOGICAL ASPECTS OF WOMEN’S REPRODUCTIVE HEALTH - Sirakovska, Olena (PSYCHOLOGICAL JOURNAL, 2018)
The article covers the concept of reproductive health, explains the need to guarantee conditions for safe motherhood, promote reproductive health among young people, improve the family planning system in Ukraine, and maintain reproductive health of population. Analysis on the causes for unsatisfactory reproductive health state of the population in Ukraine had been done. The literature data as to the influence of psychological factors on the female reproductive system had been reviewed and psychophysiological states of women with various pathology of reproductive sphere, such as endometriosis, uterine myoma, dyshormonal disorders, infertility assessed. The article itemizes basic postulates of psychosomatic medicine and the mechanisms underlying certain somatic diseases subject to the specific emotions felt, and the models of pathogenesis in psychosomatic disorders. It had been shown that the specificity of psychosomatic disorders is connected with the psychological specificity, that is, with the individual stereotype of person's emotional response and with the psychophysiological specificity − a selective effect of emotional restraint on a particular body system. The article reviews the relevance of psychological regulative methods for emotional states of women with various reproductive pathologies. It had been underlined that harmonisation of female psychological sphere is important for achieving their reproductive health. The emphasis had been given that effective assistance for gynaecological patients must be based on knowledge of psychological links in formation of and the course of the disease as may become the targets in psychocorrective work; so the research of psychological features of women with gynaecological pathologies will allow for the psychocorrective program to be developed taking into account both maladaptive components and personal resources of sick women. It is necessary to reveal general and specific psychological features under gynaecological pathology in order to define the direction for psychocorrection and develop the effective measures to give psychological assistance to these specific patients. The article makes a suggestion as to the structural subdivisions of psychological assistance to be included in clinical institutions (maternity welfare centres, hospitals, clinics) in order to prevent development of somatic complications, first of all, in the reproductive sphere, subsequent to negative emotional states, intrapersonal and interpersonal conflicts, breakdown of family relations. It is emphasized that development of a methodological framework, that is, diagnostic and correction methods for these prevention and correctional offices, is relevant for Ukraine due to the extremely severe demographic situation in the country. These centres of psychological assistance with the developed methodological framework operating in cooperation with clinic's services in terms of planned check-ups will allow for timely detection and correction of destructive changes in psychological states of women, which will contribute to the improvement in reproductive health of the nation as a whole.